CHANGES IN ELECTROLYTE AND LIPID PROFILE IN HYPOTHYROIDISM: Life Science-Bio chemistry - MURGOD, ROOPA; SOANS, GLADYS (International Journal of Life Science and Pharma Research, 2012)
Hypothyroidism is known to affect electrolyte levels as well as lipids in circulation. Though the effect of deficiency of thyroid hormones on the lipid profile has been well established, the effect on electrolytes and certain minerals like calcium, phosphorus, magnesium is not clear and the underlying mechanisms responsible for these changes not well understood. The objective was to find out the effect of hypothyroidism on certain electrolyte & mineral levels and also on lipid profile.140 cases of overt hypothyroidism were chosen, 140 age and sex matched controls were chosen. Blood samples were collected from them and T3, T4 and TSH levels were measured. Also, Cholesterol, triglycerides, LDL, HDL, calcium, phosphorus, magnesium, sodium, potassium levels in blood was measured. It was found that cholesterol, triglyceride, LDL, HDL, magnesium and phosphorus levels were significantly elevated in hypothyroidism cases than the controls. The levels of calcium, sodium and potassium levels were significantly decreased in cases than controls. It was also found that there was a significant positive correlation between serum TSH values and total cholesterol, triglyceride, LDL, HDL, magnesium, and phosphorus levels. At the same time, there was a significant negative correlation between serum TSH values and serum sodium, potassium and calcium levels. From this study, we were able to conclude that higher the TSH levels, higher will be cholesterol, triglyceride, LDL, HDL, magnesium and phosphorus levels in blood, and lower will be the values of serum calcium, sodium and potassium levels.